Distribution of calcium-binding proteins immunoreactivity in the bottlenose dolphin entorhinal cortex - Graïc, Jean-Marie; Grandis, Annamaria; Sacchini, Simona; Tagliavia, Claudio; Salamanca, Giulia; Cozzi, Bruno; Bombardi, Cristiano (Frontiers in Neuroanatomy, 2024)
The present study describes the cytoarchitectural and immunohistochemical properties of the entorhinal cortex of the bottlenose dolphin. This anatomical structure can be divided into two main areas: lateral entorhinal area (LEA) and medial entorhinal area (MEA). Using Nissl staining, we identified six layers in both the LEA and MEA. The main difference between LEA and MEA is observed in layers II and III: the neurons in layer II of the LEA were denser and larger than the neurons in layer II of MEA. In addition, we observed a relatively cell-free zone between layers II and III in LEA, but not in MEA. The immunohistochemical distribution of three calcium-binding proteins (CBPs), calbindin D-28k (CB), calretinin (CR) and parvalbumin (PV) was examined. Each calcium-binding protein exhibited a distinct laminar distribution. The immunostaining pattern of CR, on one side, and CB/PV, on the other side, appeared to be distributed in a complementary manner. PV and CB immunostaining was particularly evident in layers II and III, whereas CR immunoreactive neurons were distributed throughout all layers, especially in layers V and VI. Immunoreactivity was expressed by neurons belonging to different morphological classes: All CBPs were expressed in non-pyramidal neurons, but CB and CR were also found in pyramidal neurons. The morphological characteristics of pyramidal and non-pyramidal neurons in the dolphin entorhinal cortex are similar to those described in the entorhinal cortex of other species, including primates and rodents. Interestingly, in primates, rodents, and dolphins, most of the CBP-containing neurons are found in the superficial layers, but the large CR-ir neurons are also abundant in the deep layers. Layers II and III of the entorhinal cortex contain neurons that give rise to the perforant pathway, which conveys most of the cortical information to the hippocampal formation. From the hippocampal formation, reciprocal projections are directed back to the deep layer of the entorhinal cortex, which distributes the information to the neocortex and subcortical area. Our data reveal that in the dolphin entorhinal cortex, the three major CBPs label morphologically heterogeneous groups of neurons that may be involved in the information flow between entorhinal input and output pathways.